2016
DOI: 10.1177/0898264316645547
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Cost of Disability Transitions in Medicare

Abstract: Interventions aimed at preventing disability progression and efforts to restore functional capacity are promising strategies for containing costs and generating savings for Medicare. Future research is needed to assess the longer term impact of disability in association with the progression of chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Previous studies have shown that, for example, the proportion of individuals with multimorbidity increases with age, and multimorbidity is therefore highly prevalent in very old adults . Moreover, several other studies have specifically reported the association between multimorbidity, higher functional impairment, cognitive decline, and increased health care use or costs in older people as well, which is in accordance with our findings. Previous research suggests that anxiety and depression have a comparatively earlier onset and that anxiety and depression levels are not necessarily stable over time.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that, for example, the proportion of individuals with multimorbidity increases with age, and multimorbidity is therefore highly prevalent in very old adults . Moreover, several other studies have specifically reported the association between multimorbidity, higher functional impairment, cognitive decline, and increased health care use or costs in older people as well, which is in accordance with our findings. Previous research suggests that anxiety and depression have a comparatively earlier onset and that anxiety and depression levels are not necessarily stable over time.…”
Section: Discussionsupporting
confidence: 92%
“…The average earnings of people who have been disabled for 10 years dropped by 77% ( 10 ). Dai et al further suggested that the health expenditures of older adults with functional limitations are higher compared with those with chronic diseases alone ( 12 ). Some studies found that older adults with disabilities are the most vulnerable to poverty and ill health.…”
Section: Introductionmentioning
confidence: 99%